Bt Toxin Modification for Enhanced Efficacy - Deist, Benjamin R. (MDPI, 2014)
Insect-specific toxins derived from Bacillus thuringiensis (Bt) provide a valuable resource for pest suppression. Here we review the different strategies that have been employed to enhance toxicity against specific target species including those that have evolved resistance to Bt, or to modify the host range of Bt crystal (Cry) and cytolytic (Cyt) toxins. These strategies include toxin truncation, modification of protease cleavage sites, domain swapping, site-directed mutagenesis, peptide addition, and phage display screens for mutated toxins with enhanced activity. Toxin optimization provides a useful approach to extend the utility of these proteins for suppression of pests that exhibit low susceptibility to native Bt toxins, and to overcome field resistance.